Surveillance Robo Car Using ESP32 CAM Module - Prof. Dr. Kaushika Patel; Meghsinh Gadaria; Krisha Kansagra (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Security solutions that can be operated remotely and autonomously have become more and more necessary as surveillance technology has advanced so quickly. Although they work well for static monitoring, traditional CCTV systems are not mobile, flexible, or able to intervene in real time as needed in dynamic environments. In order to overcome these constraints, the "Surveillance Robo Car Using ESP32 CAM Module" project combines a robotic car with an ESP32 CAM module that can transmit live video over Wi-Fi. Through a web-based interface, this system allows for remote monitoring, providing an economical and effective solution for military reconnaissance, industrial monitoring, security surveillance, and search and rescue missions. With support for Bluetooth and Wi-Fi, the ESP32 CAM module offers a small and effective video streaming solution. It also offers the possibility of AI-based applications like facial recognition and motion detection. Through remote control via a web interface, the robotic platform's real-time maneuverability ensures flexibility in a range of surveillance scenarios. To ensure smooth operation, the system architecture consists of a microcontroller, motor drivers, power management units, and wireless connectivity modules. Notwithstanding its benefits, issues like power consumption, network latency, and environmental restrictions still exist. Cloud-based data storage, AI-driven threat detection, and 5G integration to boost speed and dependability are possible future improvements. This project adds to the expanding trend of autonomous security solutions thanks to recent developments in IoT and smart surveillance, opening the door for more intelligent and responsive monitoring systems.